Feminisme Kisah Maryam dalam al-Qur'ān dan Rekonstruksi Pemahaman Gender Perspektif Pragmatik - Fathurrosyid Fathurrosyid (Islamica: Jurnal Studi Keislaman, 2016)
This article discusses the story of Maryam in the Qur'ān with a pragmatic approach. This is because Maryam is textually a phenomenal figure, she even overcomes the social status of women such as Āishah and Fāṭimah, so the name is documented in a special chapter popularly known as Surat Maryam. The article concludes that the construction of the theory of pragmatics against the Qur'ān is a discipline that examines the Qur'ān from the perspective of the relationship between linguistic context that is both dyadic and non-linguistic context that is triadic. The form of feminism is the story of Mary in the perspective of speech acts and implicatures in pragmatic approach of the Qur'ān that includes access to voice disappointment and resistance against misogynistic traditions contained in Q.S. Āli 'Imrān [03]: 36, gets access to educational rights contained in Q.S. Āli 'Imrān [03]: 37, access to implement spiritual teachings in public areas in Q.S. Āli 'Imrān [03]: 43, access to performs an injunction against the practice of sexual harassment in Q.S. Maryam [19]: 18 and a motherâ€™s responsibility to provide security and comfort for the baby so that the baby did not die of starvation due to malnutrition he suffered.